The cranial and cervical muscles of the South African limbless lizard Typhlosaurus aurantiacus aurantiacus Peters (Reptilia: sauria) - Van den Heever, Jurgens Abraham (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1975.